Exploring mass variations in the Earth system. Issue 1 (1st January 2016) - Sips, Mike; Unger, Andrea; Rawald, Tobias; Sasgen, Ingo
Abstract: Geophysical processes cause a redistribution of masses within system Earth called mass transport. This mass transport induces variations in the observed gravity field of the Earth. A common scientific approach to draw conclusions about geophysical processes is to determine the imprint of individual geophysical processes in observed gravity field variations. For this purpose, modelers follow a sequence of specialized steps. From this sequence, we identified in close collaboration with Earth system modelers at the German Research Center for GeoSciences (GFZ) steps that can significantly benefit from Visual Analytics: (a) finding an applicable release of observed gravity field variations that exhibit the geophysical process of interest (b) separating individual geophysical processes in observed gravity field variations and (c) confirming the reduction of observed gravity field variations to the geophysical process of interest. We identified important analytical requirements for our Visual Analytics approach based on a user- and task-centered design. By providing tailored support for the identified requirements, our Visual Analytics approach provides a valuable expansion of the modeler's toolbox.